Internal inertia-gravity waves in the tropical lower stratosphere observed by the Arecibo Radar - Maekawa, Yasuyuki (1984)
High-resolution upper tropospheric and lower stratospheric (5-30 km) wind data were obtained during three periods from 1979 to 1981 with the aid ofthe high-power UHF radar at Arecibo, Puerto Rico (18.4°N, 66.8°W). A quasi-periodic wind oscillation with ai;t apparent period of 20-50 h was observed between 16 and 20 km in every experiment.The amplitude of both zonal and meridional wind components was ~2 m s-1, and the vertical wavelength ~2 km. The direction of the wind associated with this oscillation rotated clockwise with time, as seen for inertia-gravity waves in the Northern Hemisphere. The wave disappeared near 20 km where the mean zonal flow had easterly shear with height. This phenomenon is discussed in terms of wave absorption at a critical leve!. lt is suggested that the wave had a westward horizontal phase speed of 10-20 m s-1. The intrinsic period and the horizontal wavelength at the wave-generated height are, inferred to be 20-30 h and ~2000 km, respectively, from the relationship based on f plan e theory that the Doppler-shifted wave frequency approaches the Coriolis frequency at the critical level. The vertical group velocity estimated from the dispersion equation on the fplane closely agrees with the ascending rate of the observed wave packets at each height. In addition, each observation showed the presence of another type of oscillation with somewhat longer vertical wavelength in the lower stratosphere. If we assume the same intrinsic period and horizontal scale for this oscillation as for the abovementioned smaller vertical-scalé wave at the tropopause level, the observed period and vertical structure are well described in terms o( an internal inertia-gravity wave propagating to the opposite side in the horizontal plane.